LANGUAGE MAINTENANCE AND SOLIDARITY AMONG AFRICAN AMERICANS - Sastika Seli (Universitas Negeri Padang, 2015)
This article aims to explain the language phenomena in sociolinguistics. namely, Ianguage maintenance and solidarity. Language maintenance is the phenomena u'here the speakers of the language maintain to use the language without affected by other languages nearby. This language maintenance may be influenced by solidarity inside the language community. The analysis derived from my previous research of